Postoperative Deep Gluteal Syndrome After Hip Arthroscopic Surgery. Issue 9 (28th September 2020) - Uchida, Soshi; Kizaki, Kazuha; Hirano, Fumitaka; Martin, Hal David; Sakai, Akinori
Background: Deep gluteal syndrome (DGS) is an uncommon source of buttock and groin pain, resulting from entrapment of the sciatic nerve in the deep gluteal space. The incidence and risk factors of postoperative DGS after primary hip arthroscopic surgery are currently unknown. Purpose: To investigate the incidence and risk factors of postoperative DGS after primary hip arthroscopic surgery. Study Design: Case-control study; Level of evidence, 3. Methods: This study reviewed 1167 patients who underwent arthroscopic surgery between 2010 and 2018 by a single surgeon at a single center in Japan. DGS was defined using the seated piriformis stretch test, active hamstring test, and evidence of a hypertrophic sciatic nerve on magnetic resonance imaging. Overall, 11 of 1167 patients were diagnosed with DGS postoperatively. The DGS group (n = 11) was compared with the non-DGS group (n = 1156). Patient age, sex, body mass index (BMI), generalized joint laxity (GJL; Beighton score >6), number of hip arthroscopic procedures, and radiographic parameters including lateral center-edge angle, Sharp angle, vertical center anterior angle, Tönnis angle, alpha angle, ischiofemoral distance, ischiofemoral space, and quadratus femoris space were compared. The prevalence of developmental dysplasia of the hip (DDH) and borderline DDH (BDDH) was also compared. Logistic regression analysis was conducted to identify potential predictors for a postoperative DGS diagnosis. Results: The incidence of postoperative DGS in our study was 0.9%. Female sex (male:female ratio: 0:11 in DGS group vs 568:588 in non-DGS group; P < .01), mean number of hip surgical procedures (1.8 ± 0.9 in DGS group vs 1.1 ± 0.4 in non-DGS group; P < .01), and GJL ( P < .01) were significantly higher in the DGS group, while the mean BMI was significantly lower in the DGS group (19.8 ± 1.8 vs 22.7 ± 3.6 kg/m 2, respectively; P < .01). Radiographic parameters were not significantly different between groups. Logistic regression analysis revealed that female sex (odds ratio [OR], 22.0 [95% CI, 1.29-374.56]), multiple surgical procedures (OR, 7.8 [95% CI, 2.36-25.95]), GJL (OR, 40.9 [95% CI, 8.74-191.70]), lower BMI (OR, 0.77 [95% CI, 0.644-0.914]), and DDH/BDDH (OR, 18.1 [95% CI, 2.30-142.10]) were potential predictors of postoperative DGS. Conclusion: The incidence of postoperative DGS in our study was 0.9%. The predictors for postoperative DGS after hip arthroscopic surgery were female sex, GJL, multiple hip surgical procedures, and DDH/BDDH. Although hip arthroscopic surgery can provide favorable clinical outcomes, surgeons should be aware of the risk factors for DGS as a complication of hip arthroscopic surgery.